LPWA-based IoT Technology Selection for Smart Metering Deployment in Urban and Sub Urban Areas: A State Electricity Company Perspective - Amriane Hidayati; Muhammad Imam Nashiruddin (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2020)
The need for LPWA-based Internet of Things (IoT) technology for deploying smart metering services is rapidly growing for its ability to manage energy usage in real-time and increase efficiency. However, the problem faced by electric utility companies is how to choose the most appropriate technology. This study uses a techno-economic approach to compare the two most widely used technological alternatives, namely establishing LoRaWAN as a non-licensed LPWA technology or leasing NB-IoT as a licensed LPWA technology owned by a telecommunications operator. Case studies conducted in the urban area of Bandung and sub-urban city of Tasikmalaya as an example of a typical town in Indonesia. The results showed that LoRaWAN and NB-IoT are both technically and business feasible to be implemented with their respective advantages. LoRaWAN is superior in battery lifetime, business model, speed of implementation, and total costs, whereas NB-IoT is superior in range, capacity, quality of service, security, and ecosystem support. Using PLN's perspective as a national electricity company in Indonesia, LoRaWAN has a Net Present Value of 23% higher than NB-IoT in the 10th year.